Composite particles for nonaqueous secondary battery electrodes, negative electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
By adding electrode active substances, water-soluble polymers and binder compositions to the composite particles, and ensuring that the particle size maintenance rate reaches more than 70%, the crushing problem of composite particles during air transport is solved and the productivity of secondary batteries is improved and electrical characteristics.
Patent Information
- Application Number
- CN202380051907.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-07
AI Technical Summary
The existing composite particles are prone to breaking during air transport, resulting in a decrease in the fluidity of the electrode composite material layer and affecting the productivity and electrical characteristics of the secondary battery.
The composite particles containing electrode active substances, water-soluble polymers and binder compositions have a particle size maintenance rate of more than 70%. The dry integral particle size is measured by laser diffraction scattering method to ensure the strength and air resistance of the composite particles. Conveyor performance.
It effectively suppresses the breakage of composite particles during air transport, improves the flowability of the electrode composite material layer and the productivity of the secondary battery, and optimizes the electrical characteristics.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The present invention relates to composite particles for non-aqueous secondary battery electrodes, a negative electrode for non-aqueous secondary batteries, and a non-aqueous secondary battery. Background Art
[0002] Non-aqueous secondary batteries such as lithium-ion secondary batteries (hereinafter sometimes referred to as "secondary batteries") are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used in a wide range of applications. Therefore, in order to further improve the performance of secondary batteries, research is being conducted on the improvement of battery components such as electrodes.
[0003] For example, Patent Document 1 proposes a non-aqueous secondary battery electrode binder composition, which includes a granular polymer having a core-shell structure, wherein the core and shell of the granular polymer each include a specified monomer unit at a specified ratio, and the swelling degree of the granular polymer in the electrolyte is below a specified value. In addition, according to Patent Document 1, it is reported that the electrical properties of the secondary battery can be improved by using an electrode manufactured using the non-aqueous secondary battery electrode binder composition.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent document 1: Japanese Patent No. 7054623. Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, as one of the methods for manufacturing electrodes for secondary batteries, a powder molding method is known. The powder molding method refers to the following manufacturing method: preparing composite particles containing electrode active materials, etc., supplying the composite particles to a current collector, and further rolling and molding according to expectations, thereby forming an electrode composite material layer composed of the composite particles to obtain a secondary battery electrode.
[0009] Therefore, the inventor focuses on the manufacturing method of the secondary battery using the powder molding method. In order to improve the productivity of the secondary battery, the obtained composite particles are transported to the molding / pressing process as the next process by air transport through a conveying pipe. However, according to the research of the inventor, it is clear that the existing composite particles are sometimes broken when air transport is performed. In addition, it is also clear that due to the crushing of the composite particles, small particles will be produced, so that the fluidity of the composite particles is reduced, therefore, the obtained electrode composite material layer produces poor molding such as deviation of the mass per unit area, and the productivity of the secondary battery will be reduced.
[0010] Therefore, an object of the present invention is to provide composite particles for nonaqueous secondary battery electrodes, which are suppressed from being broken during air transportation and can improve the productivity of nonaqueous secondary batteries.
[0011] Another object of the present invention is to provide a negative electrode for a nonaqueous secondary battery using the composite particles for a nonaqueous secondary battery electrode of the present invention, and a nonaqueous secondary battery having the negative electrode for a nonaqueous secondary battery.
[0012] Solutions for solving problems
[0013] The present inventors have conducted in-depth research for the purpose of solving the above problems. Then, the present inventors have newly discovered that composite particles containing an electrode active material, a water-soluble polymer and a binder composition and having a particle size maintenance rate of 70% or more obtained by a prescribed method have excellent strength and can suppress breakage caused by air transportation, thereby completing the present invention.
[0014] That is, the object of the present invention is to advantageously solve the above-mentioned problems. According to the present invention, composite particles for non-aqueous secondary battery electrodes as described below [1] to [4], a negative electrode for non-aqueous secondary batteries as described below [5], and a non-aqueous secondary battery as described below [6] can be provided.
[0015] [1] A composite particle for a non-aqueous secondary battery electrode, comprising an electrode active material, a water-soluble polymer and a binder composition, wherein in a dry integrated particle size measurement using a laser diffraction scattering method, when the volume-based median particle size (D50) of the composite particle for a non-aqueous secondary battery electrode when the pressure of the dispersion air during the measurement is 0.25 MPa is set to D50(A), and when the volume-based median particle size (D50) of the composite particle for a non-aqueous secondary battery electrode when the pressure of the dispersion air during the measurement is 0.00 MPa is set to D50(B), the particle size maintenance rate of the composite particle represented by the following formula is 70% or more.
[0016] .
[0017] As such, the composite particles for non-aqueous secondary battery electrodes containing an electrode active material, a water-soluble polymer and a binder composition and having a particle size maintenance rate of more than 70% have excellent strength, and the breakage caused by air transportation is suppressed. Therefore, if the composite particles for non-aqueous secondary battery electrodes of the present invention are used, the fluidity of the composite particles during air transportation can be improved, thereby improving the productivity of non-aqueous secondary batteries.
[0018] In the present invention, "D50(A) particle size" and "D50(B) particle size" can be measured by the method described in Examples of the present specification.
[0019] [2] The composite particles for nonaqueous secondary batteries according to [1] above, wherein the water-soluble polymer has a carboxyl group.
[0020] As described above, when the water-soluble polymer has a carboxyl group, the electrical characteristics of the non-aqueous secondary battery can be improved.
[0021] [3] The composite particles for non-aqueous secondary batteries according to [1] or [2], wherein the binder composition comprises a polymer containing an aliphatic conjugated diene monomer unit.
[0022] As described above, when the binder composition contains a polymer containing an aliphatic conjugated diene monomer unit, the electrical characteristics of the non-aqueous secondary battery can be further improved.
[0023] [4] The composite particle for a non-aqueous secondary battery according to any one of [1] to [3] above, wherein the electrode active material is a negative electrode active material, and the negative electrode active material contains a silicon-based active material.
[0024] As described above, when the electrode active material contains a silicon-based negative electrode active material, the capacity of the non-aqueous secondary battery can be increased.
[0025] [5] A negative electrode for a non-aqueous secondary battery, comprising an electrode composite material layer formed using the composite particles for a non-aqueous secondary battery electrode according to [4] above.
[0026] In this way, the non-aqueous secondary battery negative electrode having an electrode composite material layer formed using the non-aqueous secondary battery electrode composite particles described above [4] can suppress molding defects such as deviation in unit area mass. Therefore, if the non-aqueous secondary battery electrode described above is used, the electrical characteristics of the non-aqueous secondary battery can be improved.
[0027] [6] A non-aqueous secondary battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode is the negative electrode for the non-aqueous secondary battery of [5].
[0028] As described above, a non-aqueous secondary battery comprising a positive electrode, a negative electrode, an electrolyte solution and a separator, wherein the negative electrode is the negative electrode for a non-aqueous secondary battery of [5], has excellent electrical characteristics.
[0029] Effects of the Invention
[0030] According to the present invention, it is possible to provide composite particles for nonaqueous secondary battery electrodes in which breakage during air transportation is suppressed, thereby improving the productivity of nonaqueous secondary batteries.
[0031] Furthermore, according to the present invention, there can be provided a nonaqueous secondary battery negative electrode using the composite particles for a nonaqueous secondary battery electrode of the present invention, and a nonaqueous secondary battery having the nonaqueous secondary battery negative electrode. DETAILED DESCRIPTION
[0032] Hereinafter, embodiments of the present invention will be described.
[0033] Here, the composite particles for non-aqueous secondary battery electrodes of the present invention can be used as a component of an electrode composite material layer in an electrode of a non-aqueous secondary battery such as a lithium ion secondary battery. In addition, the negative electrode for a non-aqueous secondary battery of the present invention has an electrode composite material layer formed using the composite particles for non-aqueous secondary battery electrodes of the present invention. Furthermore, the non-aqueous secondary battery of the present invention has a negative electrode for a non-aqueous secondary battery of the present invention.
[0034] (Composite particles for non-aqueous secondary battery electrodes)
[0035] The composite particles for non-aqueous secondary battery electrodes of the present invention (hereinafter also referred to as "composite particles") include an electrode active material, a water-soluble polymer and a binder composition, and optionally can further include a conductive material. Moreover, the composite particles of the present invention are characterized in that the particle size maintenance rate of the composite particles represented by the following formula is 70% or more.
[0036] .
[0037] Here, the above-mentioned D50(A) particle size is the volume-based median particle size (D50) of the composite particles when the pressure of the dispersing air during the measurement is 0.25 MPa in the dry integrated particle size measurement performed using the laser diffraction scattering method, and the above-mentioned D50(B) particle size is the volume-based median particle size (D50) of the composite particles when the pressure of the dispersing air during the measurement is 0.00 MPa in the dry integrated particle size measurement performed using the laser diffraction scattering method.
[0038] Moreover, in the present invention, the particle size maintenance rate of the composite particles is more than 70%, preferably more than 75%, and more preferably more than 80%. If the particle size maintenance rate of the composite particles is more than 70%, the strength of the composite particles is excellent, and the crushing of the composite particles caused by air transportation is suppressed. Therefore, if the composite particles of the present invention are used, the fluidity of the composite particles during air transportation can be improved, and the productivity of the secondary battery can be improved.
[0039] <Electrode Active Material>
[0040] The electrode active material contained in the composite particles is not particularly limited, and known electrode active materials used in secondary batteries can be used. In addition, for example, when the secondary battery is a lithium ion secondary battery, a substance capable of inserting and removing lithium is generally used as the electrode active material.
[0041] In addition, below, a case where the secondary battery is a lithium ion secondary battery will be described as an example, but the present invention is not limited to the following example.
[0042] Examples of negative electrode active materials for lithium ion secondary batteries include carbon-based active materials, silicon-based active materials, metal-based active materials, and negative electrode active materials obtained by combining these.
[0043] <<Carbon-based active materials>>
[0044] Here, the carbon-based active material refers to an active material having a carbon-based skeleton into which lithium can be inserted (also referred to as "doped"). Examples of the material of the carbon-based active material include carbonaceous materials and graphite materials.
[0045] Examples of the carbonaceous material include easily graphitizable carbon whose carbon structure is easily changed depending on the heat treatment temperature, and hardly graphitizable carbon having a structure close to an amorphous structure, such as glassy carbon.
[0046] Examples of graphitizable carbon include carbon materials made from tar pitch obtained from petroleum or coal, and specific examples include coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fibers, and pyrolysis vapor-grown carbon fibers.
[0047] Examples of the hardly graphitizable carbon include phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin sintered bodies (PFA), and hard carbon.
[0048] Examples of the graphite material include graphites such as natural graphite and artificial graphite.
[0049] <<Silicon-based active materials>>
[0050] Examples of the silicon-based active material include silicon (Si), alloys containing silicon, SiO, SiO x , a composite of a Si-containing material and conductive carbon, etc., in which a Si-containing material is coated or composited with conductive carbon.
[0051] Examples of the alloy containing silicon include alloy compositions containing silicon, aluminum, and transition metals such as iron, and further containing rare earth elements such as tin and yttrium.
[0052] SiO xIt is a compound containing at least one of SiO and SiO2 and Si, and x is usually greater than 0.01 and less than 2. x For example, it can be formed by utilizing a disproportionation reaction of silicon monoxide (SiO). x It can be prepared by heat treating SiO in the presence of a polymer such as polyvinyl alcohol to generate silicon and silicon dioxide. In addition, the heat treatment can be carried out at a temperature of 900° C. or more, preferably 1000° C. or more, in an atmosphere containing organic gas and / or steam, after the SiO and the optional polymer are crushed and mixed.
[0053] <<Metallic Active Materials>>
[0054] A metal-based active material refers to an active material containing a metal, and is generally an active material containing an element capable of inserting lithium in the structure, and having a theoretical capacity of 500 mAh / g or more per unit mass when lithium is inserted. As a metal-based active material, for example, lithium metal, a metal element capable of forming a lithium alloy (for example, Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.) and its alloy, and their oxides, sulfides, nitrides, silicides, carbides, phosphides, etc. can be used.
[0055] The above-mentioned negative electrode active material can be used alone or in combination of two or more. Moreover, the negative electrode active material preferably contains a silicon-based active material. If a negative electrode active material containing a silicon-based active material is used, the capacity of the obtained secondary battery can be increased.
[0056] Moreover, when the negative electrode active material includes a silicon-based active material, the proportion of the silicon-based active material in the negative electrode active material is preferably 3% by mass or more, and more preferably 5% by mass or more. If the proportion of the silicon-based active material in the negative electrode active material is 3% by mass or more, the capacity of the secondary battery obtained can be further increased.
[0057] <Content of Electrode Active Material>
[0058] Moreover, when the total mass of the composite particles is taken as 100% by mass, the content of the electrode active material in the composite particles is preferably 88% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, preferably 99% by mass or less. If the content of the electrode active material in the composite particles is above the above lower limit, the secondary battery obtained can be further high-capacitated. In addition, if the content of the electrode active material in the composite particles is below the above upper limit, the cohesion between the current collector and the composite particles can be improved.
[0059] <Water-soluble polymer>
[0060] The water-soluble polymer contained in the composite particles is a component that can prevent the components contained in the composite particles from being separated from the composite particles together with the binder composition, and can well bind the electrode composite material layer composed of the composite particles to the current collector.
[0061] Here, in the present invention, the polymer being "water-soluble" means that when 0.5 g of the polymer is dissolved in 100 g of water at a temperature of 25° C., the insoluble content is less than 1.0% by mass.
[0062] <<Composition of water-soluble polymer>>
[0063] The water-soluble polymer is not particularly limited, and examples thereof include: cellulose compounds such as carboxymethyl cellulose (CMC), carboxyethyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxypropyl cellulose, carboxyethyl methyl cellulose, and cellulose-based polymers such as their ammonium salts, alkali metal salts, etc.; oxidized starch, starch phosphate; casein; various modified starches; polyethylene oxide, polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, polysulfonic acid, polycarboxylic acid; (meth)acrylic acid copolymers, (meth)acrylamide-based polymers, and their ammonium salts, alkali metal salts, etc.
[0064] These can be used alone or in combination of two or more.
[0065] Among them, as the water-soluble polymer, cellulose polymers, (meth)acrylic acid copolymers, (meth)acrylamide polymers and combinations thereof are preferred. In the present invention, (meth)acryl refers to acryl and / or methacryl.
[0066] Furthermore, the water-soluble polymer more preferably has a carboxyl group. If the water-soluble polymer has a carboxyl group, the electrical characteristics of the secondary battery can be improved.
[0067] <Content of water-soluble polymer>
[0068] Moreover, when the total mass of the composite particles is taken as 100% by mass, the content of the water-soluble polymer in the composite particles is preferably 0.5% by mass or more, preferably 5% by mass or less, more preferably 4% by mass or less, and further preferably 3% by mass or less. If the content of the water-soluble polymer in the composite particles is above the above lower limit, the cohesion between the current collector and the composite particles can be further improved. In addition, if the content of the water-soluble polymer in the composite particles is below the above upper limit, the electrical characteristics of the secondary battery can be further improved.
[0069] <Adhesive Composition>
[0070] The adhesive composition contains at least a polymer and optionally contains other components. The shape of the polymer contained in the adhesive composition is not particularly limited, but is preferably in a granular form.
[0071] <<Polymer>>
[0072] The polymer contained in the binder composition is a component that can prevent the components contained in the composite particles from being separated from the composite particles and can well bind the electrode composite material layer composed of the composite particles to the current collector.
[0073] The polymer contained in the binder composition is not particularly limited as long as it has a composition different from the above-mentioned water-soluble polymer. For example, any polymer such as a conjugated diene polymer, an acrylic polymer, etc. can be used. Among them, the polymer contained in the binder composition preferably contains an aliphatic conjugated diene monomer unit as the main structural unit, and more preferably contains an aromatic vinyl monomer unit and an aliphatic conjugated diene monomer unit as the main structural unit. If the binder composition contains a polymer containing an aliphatic conjugated diene monomer unit, the electrical properties of the secondary battery can be further improved.
[0074] Here, “comprising aromatic vinyl monomer units and aliphatic conjugated diene monomer units as main structural units” means that in the polymer, the total content of the aromatic vinyl monomer units and aliphatic conjugated diene monomer units exceeds 50% by mass of all monomer units constituting the polymer.
[0075] In the present invention, the statement that a polymer “contains a monomer unit” means that “a polymer obtained using the monomer contains a repeating unit derived from the monomer”.
[0076] The content ratio of the monomer units in the polymer can be used 1 The determination was carried out by nuclear magnetic resonance (NMR) methods such as H-NMR.
[0077] -Aromatic vinyl monomer unit-
[0078] In addition, as the aromatic vinyl monomer capable of forming the aromatic vinyl monomer unit, for example, styrene, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinylnaphthalene, vinyltoluene, chlorostyrene, etc. can be mentioned. Among these, styrene is preferred. These can be used alone or in combination of two or more.
[0079] Furthermore, when the total of all monomer units constituting the polymer is taken as 100% by mass, the content ratio of the aromatic vinyl monomer unit in the polymer is preferably 20% by mass or more and 79% by mass or less.
[0080] -Aliphatic conjugated diene monomer unit-
[0081] In addition, as the conjugated diene monomer capable of forming the aliphatic conjugated diene monomer unit, for example, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, 2-chloro-1,3-butadiene, piperylene, etc. can be mentioned. Among these, 1,3-butadiene is preferred. These can be used alone or in combination of two or more.
[0082] Furthermore, when the total of all monomer units constituting the polymer is taken as 100% by mass, the content ratio of the aliphatic conjugated diene monomer units in the polymer is preferably 20% by mass or more and 79% by mass or less.
[0083] -Other monomer units-
[0084] The copolymer with the above-mentioned aromatic vinyl monomer unit and aliphatic conjugated diene monomer unit as main structural units may also include other monomer units except aromatic vinyl monomer unit and aliphatic conjugated diene monomer unit. As other monomer units, there is no particular limitation, and examples thereof include acidic group-containing monomer units such as unsaturated carboxylic acid monomer units, (methyl) acrylic acid ester monomer units, nitrile-containing monomer units, etc. These can be used alone or in combination of two or more.
[0085] In the present invention, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0086] Furthermore, when the total of all monomer units constituting the polymer is taken as 100% by mass, the content ratio of other monomer units in the polymer is preferably 1% by mass or more and 45% by mass or less.
[0087] =Acidic group-containing monomer unit=
[0088] As unsaturated carboxylic acid monomers capable of forming unsaturated carboxylic acid monomer units as acidic group-containing monomer units, for example, unsaturated monocarboxylic acids and their derivatives, unsaturated dicarboxylic acids and their anhydrides and their derivatives can be cited. As examples of unsaturated monocarboxylic acids, acrylic acid, methacrylic acid and crotonic acid can be cited. As examples of derivatives of unsaturated monocarboxylic acids, 2-ethyl acrylic acid, isocrotonic acid, α-acetoxy acrylic acid, β-trans-aryloxy acrylic acid, α-chloro-β-E-methoxy acrylic acid and β-diamino acrylic acid can be cited. As examples of unsaturated dicarboxylic acids, maleic acid, fumaric acid and itaconic acid can be cited. As examples of anhydrides of unsaturated dicarboxylic acids, maleic anhydride, acrylic anhydride, methyl maleic anhydride and dimethyl maleic anhydride can be cited. Examples of derivatives of unsaturated dicarboxylic acids include methyl maleic acid, dimethyl maleic acid, phenyl maleic acid, chloro maleic acid, dichloro maleic acid, fluoro maleic acid, diphenyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, fluoroalkyl maleate, etc. These can be used alone or in combination of two or more.
[0089] Among these, the unsaturated carboxylic acid monomer is preferably an unsaturated monocarboxylic acid such as acrylic acid and methacrylic acid, and an unsaturated dicarboxylic acid such as maleic acid, fumaric acid, and itaconic acid. More preferred are acrylic acid and itaconic acid, and even more preferred is itaconic acid.
[0090] =(Meth)acrylate monomer unit=
[0091] Examples of the (meth)acrylate monomer that can form the (meth)acrylate monomer unit include methyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and 2-hydroxyethyl acrylate, and these can be used alone or in combination of two or more.
[0092] =Nitrile-containing monomer unit=
[0093] As the nitrile-containing monomer capable of forming the nitrile-containing monomer unit, α, β-ethylenically unsaturated nitrile monomer can be cited. Specifically, as the α, β-ethylenically unsaturated nitrile monomer, there is no particular limitation as long as it is an α, β-ethylenically unsaturated compound having a nitrile group, and examples thereof include: acrylonitrile; α-halogenated acrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitrile such as methacrylonitrile and α-ethylacrylonitrile, etc. Among these, (meth)acrylonitrile is preferred. These can be used alone or in combination of two or more.
[0094] In the present invention, "(meth)acrylonitrile" means acrylonitrile and / or methacrylonitrile.
[0095] <<Method for preparing polymer>>
[0096] The preparation method of the above-mentioned polymer is not particularly limited, and for example, it can be prepared by polymerizing a monomer composition containing the above-mentioned monomers. Here, the content ratio of each monomer in the monomer composition for preparing the polymer can be determined according to the content ratio of each repeating unit in the polymer.
[0097] The polymerization method is not particularly limited, and any method can be used, such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. In addition, any addition polymerization such as ionic polymerization, radical polymerization, and living radical polymerization can be used as the polymerization method.
[0098] <<Other ingredients>>
[0099] As other components that can be included in the adhesive composition, there is no particular limitation, and examples thereof include defoamers, preservatives, antioxidants, reinforcing materials, leveling agents, viscosity modifiers, electrolyte additives, etc. These are not particularly limited as long as they do not affect the battery reaction, and known components can be used. In addition, these components can be used alone or in combination of two or more.
[0100] <Content of Adhesive Composition>
[0101] Moreover, when the total mass of the composite particles is taken as 100% by mass, the content of the binder composition in the composite particles is preferably 0.1% by mass or more, preferably 5% by mass or less, more preferably 4% by mass or less, and further preferably 3% by mass or less. If the content of the binder composition in the composite particles is above the above lower limit, the adhesion between the current collector and the composite particles can be further improved. In addition, if the content of the binder composition in the composite particles is below the above upper limit, the electrical characteristics of the secondary battery can be further improved.
[0102] <Conductive Materials>
[0103] As described above, the composite particles of the present invention may optionally further contain a conductive material. In addition, the conductive material that the composite particles of the present invention can contain is used to promote electrical contact between electrode active materials. As a conductive material, conductive carbon materials such as carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace black, etc.), graphite, carbon fiber, carbon flakes, etc.; fibers, foils, etc. of various metals can be used. Among them, as a conductive material, it is preferred to include carbon fibers, more preferably carbon nanotubes, carbon ultra-short fibers such as vapor-grown carbon fibers, further preferably carbon nanotubes, and particularly preferably single-walled carbon nanotubes. These can be used alone or in combination of two or more.
[0104] <Content of Conductive Material>
[0105] Moreover, when the total mass of the composite particles is taken as 100 mass %, the content of the conductive material in the composite particles is preferably 0.01 mass % or more, preferably 3 mass % or less, more preferably 2 mass % or less, and further preferably 1 mass % or less. If the content of the conductive material in the composite particles is within the above range, the electrical contact between the electrode active materials can be further promoted.
[0106] (Method for producing composite particles for non-aqueous secondary battery electrodes)
[0107] The method for producing the composite particles of the present invention is not particularly limited, and for example, it may include a step of spray drying a slurry composition comprising at least an electrode active material, a water-soluble polymer, a binder composition and a solvent, and further comprising a conductive material as required (spray drying step), and may optionally further include other steps such as a step of classifying the obtained composite particles (classification step). Each step is described below.
[0108] <Spray Drying Process>
[0109] In the spray drying step, the slurry composition is spray-dried to obtain composite particles. The spraying step is a method of spraying and drying the slurry composition in hot air to obtain granules.
[0110] The temperature of the hot air during spray drying is preferably 25 to 250° C., more preferably 50 to 220° C., and further preferably 80 to 200° C. In the spray drying method, the method of blowing the hot air is not particularly limited, and examples thereof include: a method in which the hot air flows in parallel with the spray direction in a lateral direction; a method in which the hot air is sprayed at the top of the drying tower and falls together with the hot air; a method in which the sprayed droplets contact the hot air in countercurrent; a method in which the sprayed droplets initially flow in parallel with the hot air and then contact the hot air in countercurrent due to gravity drop, etc.
[0111] The temperature of the slurry composition to be sprayed is not limited, and may be room temperature or may be heated to a temperature higher than room temperature.
[0112] Spray drying can be performed using a known spray dryer.
[0113] Here, the device used for spraying the slurry composition is not particularly limited, and examples thereof include a sprayer, etc. Examples of the sprayer include a rotating disk type, a cup type, a two-fluid nozzle type, and a pressurized type.
[0114] <<Slurry Composition>>
[0115] Moreover, the slurry composition used in the spray drying process comprises an electrode active material, a water-soluble polymer, a binder composition and a solvent, and can further comprise other components and a conductive material as required. In addition, as the electrode active material, the water-soluble polymer, the binder composition, other components and the conductive material, those described in the item of the above-mentioned "composite particles for non-aqueous secondary battery electrodes of the present invention" can be used.
[0116] As the solvent used in the slurry composition, there is no particular limitation, and any one of water and an organic solvent can be used. As the organic solvent, for example, acetonitrile, N-methyl-2-pyrrolidone, tetrahydrofuran, acetone, acetylpyridine, cyclopentanone, dimethylformamide, dimethyl sulfoxide, methylformamide, methyl ethyl ketone, furfural, ethylenediamine, dimethylbenzene (xylene), methylbenzene (toluene), cyclopentyl methyl ether and isopropanol can be used. In particular, water is preferably used.
[0117] Furthermore, these solvents can be used alone or in combination of two or more at an optional mixing ratio.
[0118] <<Method for preparing slurry composition>>
[0119] The method for preparing the slurry composition is not particularly limited, and the slurry composition can be prepared, for example, by adding the electrode active material, water-soluble polymer, binder composition, solvent, and other components and conductive materials used as needed to a solvent and mixing them.
[0120] Moreover, from the viewpoint of further improving the strength of the obtained composite particles and improving the yield of the composite particles, the preparation method of the slurry composition preferably includes a dry mixing step. In addition, in the present invention, "dry mixing" refers to mixing the components in a state where the solid content concentration is higher than that of the final slurry composition.
[0121] Specifically, the preparation method of the above-mentioned slurry composition can include, for example: a dry mixing process of mixing an electrode active material, a water-soluble polymer, optional other components and a conductive material; and a preparation process of adding a binder composition to the mixture obtained by the dry mixing process and further mixing to prepare the slurry composition.
[0122] Here, the method for mixing the above-mentioned components in the above-mentioned dry mixing step is not particularly limited, but it is preferable to perform mixing using a planetary mixer.
[0123] The solid content concentration of the mixture obtained in the dry mixing step is preferably 60% by mass or more, more preferably 62% by mass or more, further preferably 65% by mass or more, and is preferably 80% by mass or less, more preferably 75% by mass or less, further preferably 70% by mass or less.
[0124] In addition, the method for mixing the above-mentioned components in the above-mentioned preparation step is not particularly limited, but mixing using a planetary mixer is preferred.
[0125] The solid content concentration of the mixed solution (ie, slurry composition) obtained after the preparation step is preferably 40% by mass or more, more preferably 42% by mass or more, further preferably 44% by mass or more, and preferably less than 60% by mass.
[0126] <Classification process>
[0127] The classification process is a process for classifying the composite particles obtained by the spray drying process. The classification method is not particularly limited, and can be: dry classification methods such as gravity classification, inertial classification, and centrifugal classification; wet classification methods such as sedimentation classification, mechanical classification, and hydraulic classification; classification methods such as sieving classification using a sieve such as a vibrating screen and an in-plane motion screen. The sieving classification method is particularly preferred. By performing the classification process, the desired composite particles can be easily obtained.
[0128] (Non-aqueous secondary battery negative electrode)
[0129] The negative electrode for a non-aqueous secondary battery of the present invention (hereinafter also referred to as "negative electrode") has an electrode composite material layer. Moreover, the electrode composite material layer is formed using the composite particles for the non-aqueous secondary battery electrode of the present invention. Therefore, the negative electrode of the present invention has an excellent appearance by suppressing poor molding such as deviation of unit area mass, and can improve the electrical characteristics of the secondary battery.
[0130] In the negative electrode of the present invention, the electrode composite material layer is, for example, arranged on the current collector possessed by the electrode. The electrode of the present invention may have an electrode composite material layer only on one side of the current collector, or may have an electrode composite material layer on both sides. In addition, the negative electrode of the present invention may also have a layer other than the electrode composite material layer and the current collector on the surface of the negative electrode (particularly the surface on the side of the electrode composite material layer) (hereinafter referred to as "other layers"). In addition, the negative electrode of the present invention may also have other layers between the current collector and the electrode composite material layer.
[0131] <Electrode Composite Material Layer>
[0132] As described above, the electrode composite material layer is formed using the composite particles of the present invention, that is, the electrode composite material layer contains the electrode active material, the water-soluble polymer, the binder composition, and can optionally contain the other components and the conductive material.
[0133] In addition, the components contained in the electrode composite material layer are the components contained in the composite particles of the present invention described above, and the preferred existence ratios and properties of these components in the electrode composite material layer are the same as the preferred existence ratios and properties of the components in the composite particles.
[0134] <Current collector>
[0135] As the current collector, a material having conductivity and electrochemical durability can be selected and used according to the type of secondary battery. For example, as the current collector of the negative electrode for lithium ion secondary battery, a current collector composed of iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. Among them, copper foil is particularly preferred as the current collector used in the negative electrode. In addition, the above-mentioned materials can be used alone or in combination of two or more in an optional ratio.
[0136] <Other layers>
[0137] There are no particular limitations on other layers that may be optionally provided on the surface of the electrode (especially the surface on the electrode composite material layer side), and examples thereof include: a known heat-resistant layer provided for the purpose of improving heat resistance; and a known adhesive layer provided for the purpose of improving adhesion to other battery components such as separators.
[0138] In addition, other layers that may be provided between the current collector and the electrode composite material layer are not particularly limited, and examples thereof include known primer layers provided for the purpose of improving adhesion between the current collector and the electrode composite material layer.
[0139] (Method for producing negative electrode for non-aqueous secondary battery)
[0140] The manufacturing method of the negative electrode of the present invention having an electrode composite material layer composed of the above-mentioned composite particles is not particularly limited, for example, it can be manufactured by forming the above-mentioned composite particles of the present invention into a sheet, and then stacking them on a current collector. In addition, from the viewpoint of further improving the productivity of the secondary battery, it is preferred to directly press-form the composite particles on the current collector.
[0141] As a method for performing pressure molding, for example, there can be cited: using a roller pressure molding device having a pair of rollers, while conveying the current collector with the rollers, while supplying the composite particles to the roller pressure molding device with a supply device such as a screw feeder, thereby forming the electrode composite material layer on the current collector by roller pressure molding; a method of spreading the composite particles on the current collector, flattening the composite particles with a scraper, etc. and adjusting the thickness, and then molding with a pressure device, etc. Among these, the roller pressure molding method is preferred.
[0142] (Non-aqueous secondary battery)
[0143] The nonaqueous secondary battery of the present invention comprises a positive electrode, a negative electrode, an electrolyte solution and a separator, wherein the negative electrode is the negative electrode for the nonaqueous secondary battery of the present invention described above. Therefore, the secondary battery of the present invention has excellent electrical characteristics.
[0144] In addition, the following description will take a case where the nonaqueous secondary battery is a lithium ion secondary battery as an example, but the present invention is not limited to the following example.
[0145] <Positive electrode>
[0146] The positive electrode is not particularly limited, and a known positive electrode can be used. Specifically, a positive electrode obtained by forming a positive electrode composite material layer on a current collector by a known method can be used.
[0147] <Negative electrode>
[0148] As the negative electrode, the above-mentioned negative electrode for a secondary battery of the present invention is used.
[0149] <Electrolyte>
[0150] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is generally used. As the supporting electrolyte, for example, a lithium salt can be used. As the lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be cited. Among them, since they are easily soluble in solvents and show a high degree of dissociation, LiPF6, LiClO4, CF3SO3Li are preferred, and LiPF6 is particularly preferred. In addition, the electrolyte can be used alone or in combination of two or more in an optional ratio.
[0151] As the organic solvent used in the electrolyte, there is no particular limitation as long as it can dissolve the supporting electrolyte, and can be appropriately used, for example: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these solvents can also be used.
[0152] In addition, the concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. In addition, known additives such as vinylene carbonate, fluoroethylene carbonate, methyl ethyl sulfone, etc. can also be added to the electrolytic solution.
[0153] <Spacer>
[0154] As a separator, there is no particular limitation, and for example, the separators described in Japanese Patent Publication No. 2012-204303 can be used. Among these, from the aspect of being able to make the overall film thickness of the separator thinner, thereby increasing the ratio of the electrode active material in the secondary battery and increasing the capacity per unit volume, a microporous membrane composed of a polyolefin resin (polyethylene, polypropylene, polybutylene, polyvinyl chloride) is preferred.
[0155] <Method for producing lithium-ion secondary battery>
[0156] The lithium-ion secondary battery of the present invention can be manufactured, for example, by overlapping the positive electrode and the negative electrode with a spacer, winding, folding, etc. according to the shape of the battery as needed and placing it in a battery container, injecting electrolyte into the battery container and sealing it. In order to prevent the internal pressure rise of the secondary battery, overcharge and discharge, etc., it is also possible to set a fuse, PTC element, etc., an overcurrent protection element, a porous metal mesh, a guide plate, etc. as needed. The shape of the secondary battery can be, for example, any one of a coin shape, a button shape, a sheet shape, a cylindrical shape, a square shape, a flat shape, etc.
[0157] Example
[0158] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0159] <Particle Size Retention Rate of Composite Particles>
[0160] The particle size maintenance rate of the composite particles was determined using a laser diffraction scattering particle size distribution analyzer (manufactured by Microchip Biotech, Inc., “MT3200II”).
[0161] Specifically, using the laser diffraction scattering particle size distribution measuring apparatus, in the dry integrated particle size measurement using the laser diffraction scattering method, the volume-based median particle size (D50) [D50 (A) particle size] of the composite particles when the pressure of the dispersion air during the measurement is 0.25 MPa is obtained. In addition, using the laser diffraction scattering particle size distribution measuring apparatus, in the dry integrated particle size measurement using the laser diffraction scattering method, the volume-based median particle size (D50) [D50 (B) particle size] of the composite particles when the pressure of the dispersion air during the measurement is 0.00 MPa is obtained.
[0162] Then, the particle size maintenance rate of the composite particles was calculated based on the following formula: The closer the value of the particle size maintenance rate of the composite particles is to 100%, the better the strength of the composite particles is.
[0163] .
[0164] <Air transport durability of composite particles>
[0165] The composite particles were transported by air at a wind speed of 8 m / s using a high-concentration air transport device (manufactured by Toyo High-Tech Co., Ltd., "Plug Master TPM"). Then, using the same laser diffraction scattering particle size distribution measuring device as used in calculating the "particle size maintenance rate of the composite particles", a volume-based median particle size (D50) [D50 (C) particle size] of the composite particles when the pressure of the dispersion air during the measurement is 0.00 MPa was obtained in a dry integrated particle size measurement using a laser diffraction scattering method.
[0166] Then, using the volume-based D50(B) particle size of the composite particles obtained when calculating the above-mentioned "maintenance rate of composite particles" and the volume-based D50(C) particle size of the above-mentioned composite particles, the particle size maintenance rate of the composite particles before and after air transportation is calculated based on the following formula.
[0167] .
[0168] Then, the air transport durability of the composite particles was evaluated according to the following criteria.
[0169] The closer the value of the particle size maintenance rate of the composite particles before and after air transportation is to 100%, the better the air transportation durability of the composite particles is, that is, the more the breakage of the composite particles during air transportation is suppressed.
[0170] A: The particle size maintenance rate of composite particles before and after air conveying is more than 95%
[0171] B: The particle size maintenance rate of the composite particles before and after air transportation is 85% or more and less than 95%
[0172] C: The particle size maintenance rate of the composite particles before and after air conveying is less than 85%
[0173] (Example 1)
[0174] <Preparation of Negative Electrode Slurry Composition>
[0175] Into a planetary mixer with a disperser (manufactured by Plemicus, "HIVIS DISPER MIX 3D-2"), 94.5 parts of artificial graphite as a carbon-based active material and 3.0 parts of SiO as a silicon-based active material were added as negative electrode active materials. x, as a water-soluble polymer, 0.5 parts of a 1% aqueous solution of carboxymethyl cellulose sodium salt (CMC-Na) and 0.5 parts of a 4% aqueous solution of sodium polyacrylate (PAA-Na) were added in terms of solid content. Then, the mixture was adjusted to a solid content concentration of 65% with ion exchange water, and mixed at 25° C. for 60 minutes to obtain a mixed solution (dry mixing step).
[0176] Next, 1.5 parts of a 40% aqueous dispersion of a styrene-butadiene-methacrylic acid copolymer as an SBR copolymer was added to the mixed solution as a binder composition in terms of solid content. Further, ion exchange water was added to adjust the final solid content concentration of the mixed solution to 50%, and then further mixed for 10 minutes. Thereafter, the mixed solution was degassed under reduced pressure to obtain a negative electrode slurry composition.
[0177] <Production of composite particles for secondary battery electrodes>
[0178] The obtained negative electrode slurry composition was spray dried using a spray dryer (GEA, "MOBILE MINOR") under the conditions of atomizer: rotary disk type (diameter: 50 mm), rotation speed: 25000 rpm, and hot air temperature (outlet temperature): 100° C. to prepare composite particles (spray drying step). Then, the obtained composite particles were classified using a sieve with a nominal mesh size of 150 μm (JIS Z8801-1) (classification step) to obtain composite particles for secondary battery electrodes.
[0179] Using the obtained composite particles for secondary battery electrodes, the particle size maintenance rate of the composite particles and the air transport durability of the composite particles were measured and evaluated.
[0180] (Example 2)
[0181] When preparing the negative electrode slurry composition, a 1% aqueous solution of carboxymethyl cellulose sodium salt (CMC-Na) as a water-soluble polymer is not used, and a 4% aqueous solution of sodium polyacrylate (PAA-Na) is changed to 1.0 part in terms of solid content. In addition, the negative electrode slurry composition is prepared in the same manner as in Example 1 to prepare composite particles for secondary battery electrodes. Then, the particle size maintenance rate of the composite particles and the air transport durability of the composite particles are measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0182] (Example 3)
[0183] When preparing the negative electrode slurry composition, a 4% aqueous solution of a lithium salt of an acrylic acid-acrylamide copolymer (P(AA-Aam)-Li) of 1.0 parts in solid content was used instead of a 1% aqueous solution of carboxymethyl cellulose sodium salt (CMC-Na) and a 4% aqueous solution of sodium polyacrylate (PAA-Na) as a water-soluble polymer. In addition, a negative electrode slurry composition was prepared in the same manner as in Example 1 to produce composite particles for secondary battery electrodes. Then, the particle size retention rate of the composite particles and the air transport durability of the composite particles were measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0184] (Example 4)
[0185] When preparing the negative electrode slurry composition, the artificial graphite as the carbon-based active material was changed from 94.5 parts to 97.5 parts, and SiO as the silicon-based active material was not used. x . In addition, the 1% aqueous solution of carboxymethyl cellulose sodium salt (CMC-Na) as a water-soluble polymer was changed from 0.5 parts to 1.0 parts in terms of solid content, and the 4% aqueous solution of sodium polyacrylate (PAA-Na) was not used. In addition, the negative electrode slurry composition was prepared in the same manner as in Example 1 to produce composite particles for secondary battery electrodes. Then, the particle size retention rate of the composite particles and the air transport durability of the composite particles were measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0186] (Comparative Example 1)
[0187] When preparing the slurry composition for the negative electrode, the dry mixing process is not performed, and the slurry composition for the negative electrode is prepared as described below. In addition, when making composite particles for secondary battery electrodes, as the slurry composition for the negative electrode, the slurry composition for the negative electrode prepared without the dry mixing process as described below is used. In addition, the slurry composition for the negative electrode is prepared in the same manner as in Example 1 to produce composite particles for secondary battery electrodes. Then, the particle size maintenance rate of the composite particles and the air transport durability of the composite particles are measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0188] <Preparation of Slurry Composition for Negative Electrode of Lithium Ion Secondary Battery>
[0189] While 86.25 parts of water were stirred with a disperser (manufactured by Plemicus, "HOMO DISPER 2.5 Model"), 0.5 parts of a 1% aqueous solution of carboxymethyl cellulose sodium salt (CMC-Na) and 0.5 parts of a 4% aqueous solution of sodium polyacrylate (PAA-Na) were added as water-soluble polymers in terms of solid content, and then 3.0 parts of SiO as a silicon-based active material were added as an electrode active material. xand 94.5 parts of artificial graphite as a carbon-based active material, and finally, 1.5 parts of a 40% aqueous dispersion of styrene-butadiene-methacrylic acid copolymer as a binder composition in terms of solid content. Then, after mixing these mixtures at 25° C. for 60 minutes, a negative electrode slurry composition with a solid content concentration of 40% was obtained.
[0190] (Comparative Example 2)
[0191] When preparing the negative electrode slurry composition, instead of the 1% aqueous solution of carboxymethyl cellulose sodium salt (CMC-Na) and the 4% aqueous solution of sodium polyacrylate (PAA-Na) as water-soluble polymers, a 4% aqueous solution of a lithium salt of acrylic acid-acrylamide copolymer (P(AA-Aam)-Li) of 1.0 parts in terms of solid content was used. In addition, the negative electrode slurry composition was prepared in the same manner as in Comparative Example 1 to produce composite particles for secondary battery electrodes. Then, the particle size maintenance rate of the composite particles and the air transport durability of the composite particles were measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0192] (Comparative Example 3)
[0193] When preparing the negative electrode slurry composition, the artificial graphite as the carbon-based active material was changed from 94.5 parts to 97.5 parts, and SiO as the silicon-based active material was not used. x . In addition, as a water-soluble polymer, a 1% aqueous solution of carboxymethyl cellulose sodium salt (CMC-Na) was changed from 0.5 parts in terms of solid content to 1.0 parts in terms of solid content, and a 4% aqueous solution of sodium polyacrylate (PAA-Na) was not used. In addition, a negative electrode slurry composition was prepared in the same manner as in Comparative Example 1 to produce composite particles for secondary battery electrodes. Then, the particle size maintenance rate of the composite particles and the air transport durability of the composite particles were measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0194] [Table 1]
[0195] .
[0196] In Table 1,
[0197] "CMC-Na" means carboxymethyl cellulose sodium salt,
[0198] "PAA-Na" means sodium polyacrylate,
[0199] "P(AA-Aam)-Li" represents a lithium salt of acrylic acid-acrylamide copolymer.
[0200] As can be seen from Table 1, composite particles containing an electrode active material, a water-soluble polymer and a binder composition and having a particle size maintenance rate of 70% or more have excellent air transport durability and are suppressed from breaking during air transport.
[0201] Industrial Applicability
[0202] According to the present invention, it is possible to provide composite particles for nonaqueous secondary battery electrodes in which breakage during air transportation is suppressed, thereby improving the productivity of nonaqueous secondary batteries.
[0203] Furthermore, according to the present invention, there can be provided a nonaqueous secondary battery negative electrode using the composite particles for a nonaqueous secondary battery electrode of the present invention, and a nonaqueous secondary battery having the nonaqueous secondary battery negative electrode.
Claims
1. A composite particle for a non-aqueous secondary battery electrode, comprising an electrode active material, a water-soluble polymer and a binder composition, In the dry integrated particle size measurement performed by the laser diffraction scattering method, when the volume-based median particle size (D50) of the non-aqueous secondary battery electrode composite particles when the pressure of the dispersion air during the measurement is 0.25 MPa is set as the D50(A) particle size, and when the volume-based median particle size (D50) of the non-aqueous secondary battery electrode composite particles when the pressure of the dispersion air during the measurement is 0.00 MPa is set as the D50(B) particle size, the particle size maintenance rate of the composite particles represented by the following formula is 70% or more, 。 2. The composite particles for non-aqueous secondary battery electrodes according to claim 1, wherein The water-soluble polymer has a carboxyl group.
3. The composite particle for non-aqueous secondary battery electrode according to claim 1, wherein The adhesive composition comprises a polymer containing aliphatic conjugated diene monomer units.
4. The composite particles for non-aqueous secondary battery electrodes according to claim 1, wherein The electrode active material is a negative electrode active material, and the negative electrode active material includes a silicon-based active material. 5 . A negative electrode for a non-aqueous secondary battery, comprising an electrode composite material layer formed using the composite particles for a non-aqueous secondary battery electrode according to claim 4 .
6. A non-aqueous secondary battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, The negative electrode is the negative electrode for a non-aqueous secondary battery according to claim 5 .
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A